Zinc methionine or zinc sulphate supplementation modulate the development of the hypopharyngeal gland and expression of major royal jelly protein genes in Apis mellifera L. bees - do Prado Ribeiro, Giovanna [UNESP]; Kadri, Samir Moura [UNESP]; Justulin, Luis Antônio [UNESP]; Ribolla, Paulo Eduardo Martins [UNESP]; Orsi, Ricardo de Oliveira [UNESP] (Wiley, 2023)
We analysed whether the source of zinc (inorganic and organic) influences the morphology of the hypopharyngeal gland (HPG) and the relative expression of major royal jelly protein (MRJP) genes in nursing bees at 6 days of age. For this, 15 colonies of Apis mellifera bees were subjected to the following treatments: Zn0 (control), zinc methionine (50 ppm) and zinc sulphate monohydrate (50 ppm) during the off-season (characterized by food reduction). MRJP1 and MRJP5 gene expression was analysed using real-time PCR and HPG sections under a microscope. Bee mortality and population development were also evaluated for 30 days. It was observed that the honeybees consumed all sugar syrup containing zinc both in its organic and inorganic forms, which did not promote mortality or affect population development. Regarding HPG morphometry, it was observed that zinc, regardless of the source, promoted the acini area significantly greater than that of the control. Zn methionine promoted a significant increase in HPG area compared with that of an inorganic source. The relative expression of MRJP1 and MRJP5 was not significantly affected compared with the control. We conclude that the mineral Zn promotes an increase in the HPG area and does not alter the pattern of expression of the MRJP1 and MRJP5 genes, and that the organic source of the mineral presents the best results.
Keywords: beekeeping; genetics; gland area; morphology; nutrition